Implementasi Lesson Study melalui Model Cooperative Learning pada Pembelajaran IPAS di Kelas V SDN 1 Kelayu Selatan - Ainun Safitri; Donna Boedi Maritasari; Muhammad Khairul Wazni; Pitriati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Several challenges are still found in Integrated Science and Social Studies (IPAS) learning in elementary schools. Student participation is relatively low, collaboration among students has not been optimal, and teacher-centered learning methods still dominate classroom activities. Therefore, learning strategies that encourage active participation, collaboration, and student-centered learning are needed. This study aims to describe the implementation of Lesson Study through the Cooperative Learning model in IPAS learning for fifth-grade students at SDN 1 Kelayu Selatan. The study involved 28 fifth-grade students in the second semester of the 2025/2026 academic year and employed a descriptive quantitative research method. The research was carried out through the Plan, Do, and See stages. Data were collected through observations, learning achievement tests, and documentation. The data were analyzed using descriptive statistics, including activity percentages, classical learning mastery, and classical learning achievement. The results showed that the implementation of Lesson Study through the Cooperative Learning model was successfully carried out. The developed learning materials obtained a score of 95, which was categorized as very good. Teacher activities during the learning process were also rated as very good by all observers. The average student score was 93.39, with the highest score of 100 and the lowest score of 75. All students achieved the minimum mastery criteria, resulting in 100% classical learning mastery and a classical learning achievement of 93.39%. These findings indicate that the implementation of Lesson Study through the Cooperative Learning model is effective in improving both the quality of the learning process and students' learning outcomes in IPAS at the elementary school level.